Quality of College Life (QCL) of Students: A Study among Tehran and Kurdestan College Students - Leila Falahati (Taḥqīqāt-i Farhangī-i Īrān)
The main aim of present study was to examine the quality of college life (QCL) based on the model developed by Sirgy et aI., (20] 0). The research design was correlational and the sample was comprises of 400 students from three universities including Tehran, Allameh and Kurdestan, which the respondents were selected using random sampling method. Quality of college life measurement was included three main subjects about college life as satisfaction with academic aspect, social aspect and facilities and services. In order to analysis the data structural equation modeling (SEM) were employed. Findings indicated that the satisfaction with services and facilities has significant effect on satisfaction with academic and social aspects of college life. Moreover findings revealed that satisfaction with quality of college life has significant effect on satisfaction with overall life among students. Results indicated that the satisfaction with academic aspect and facilities and services among Tehran's university students is higher than Kurdestan's university students. Based on present findings the quality of universities may receive more attentions by higher education system especially in low income provinces such as Kurdestan. Lack of facilities resulted in decreasing the quality of academic aspect, social aspect and quality of college life. Low satisfaction with college life is leading to decreasing the overall life satisfaction which resulted in issues such as depression, frustration and anxiety among students.